Individual differences in working memory strategies for reading expository text - Budd, Desiree; Whitney, Paul; Turley, Kandi Jo (Memory & cognition, 1995)
This study investigated whether individual differences in working memory (WM) span are associated with different WM management strategies during the reading of expository text. In Experiment 1, probe questions were presented on line during reading to determine whether thematic information was maintained in WM throughout comprehension. The data indicated that readers across the range of WM span maintained thematic information in WM throughout the reading of a given passage. In Experiment 2, sentence reading times and accuracy for both topic and detail questions were measured in two conditions: when topic sentences were present and when topic sentences were absent. Subjects performed similarly across the range of WM span in the topic-present condition, but lower span subjects performed more poorly on detail questions in the topic-absent condition. In Experiment 3, the topic-present condition of the second experiment was replicated, except that subjects expected to receive questions about details only. Thematic processing and retention of topic and detail information all increased with span. Taken together, these results suggest that, for more difficult text processing tasks, high- and low-span subjects adopt different WM management strategies and these strategies influence what is learned from reading the text.